Determinants of complementary and integrative medicine use in inflammatory bowel disease: a focus on probiotics, prebiotics, and fermentable dietary fibres - Keshteli, Ammar H.; Chibbar, Richa; Silva, Melissa; Danois, Karen; Valcheva, Rosica; Wine, Eytan; Dieleman, Levinus A. (Frontiers in Medicine, 2025)
BackgroundComplementary and integrative medicine (CIM) modalities, particularly probiotics, prebiotics, and fermentable dietary fibers (PPF) use in IBD patients is common and increasing, particularly for symptom management. This study aimed to assess the prevalence of CIM and PPF use among IBD patients and to identify potential demographic and clinical factors associated with utilization.MethodsThis was a cross-sectional study of adult IBD patients at a tertiary IBD centre in Western Canada. A self-administered questionnaire and chart review were performed, focusing on demographic and clinical characteristics, CIM and PPF use in the past year (current) and/or lifetime, and sources of awareness about PPF products.ResultsA total of 267 patients were included, 182 with CD and 85 with UC. Overall, 89.9% of participants reported CIM use in the current year, while the current and lifetime prevalence of PPF use was 51 and 63%, respectively. UC diagnosis was associated with increased likelihood of current PPF use (OR: 1.91, 95% CI: 1.10–3.12). Holding a university degree was associated with increased likelihood of lifetime PPF use (OR: 2.21, 95% CI: 1.07–4.55). PPF awareness through gastroenterologists (OR: 3.19, 95% CI: 1.55–6.58) was significantly associated with lifetime PPF use.ConclusionUse of CIM modalities such as PPF is common among IBD patients. This study found that lifetime PPF use was associated with higher level of education and awareness through gastroenterologists. Healthcare providers, and specifically gastroenterology specialists, should routinely inquire about PPF use and educate IBD patients. Further studies are required to determine the benefit derived from these products.